BIRD DIVERSITY IN SHENDI AREA, SUDAN - Sulieman, Yassir; Pengsakul, Theerakamol; Afifi, Azzam; Mohamed A., Zakaria (International Journal of Research -GRANTHAALAYAH, 2016)
The present study was conducted from July to December 2015 and found that the Shendi area, River Nile State, Sudan, Africa, hosts considerable bird diversity with 35 species being observed belonging to 22 families; of which Columbidae, Meropidae and Nectariniidae were the most frequently observed species.